Comprehensive analysis of single-cell and bulk transcriptomes reveals key B-cell genes and immune microenvironment regulation in bladder cancer - Wang, Lijun; Yang, Juan; Xu, Zhangxiao; Tao, Bo; He, Yunpeng; Zhao, Yuan; Wu, Jian; Ma, Yiran; Zhong, Zitao; Ye, Lin (Frontiers in Immunology, 2025)
BackgroundBladder cancer is a significant malignancy, for which prognostic prediction and understanding of the tumor immune microenvironment are crucial. B cells play a key regulatory role in this environment, making their study essential for advancing bladder cancer research.MethodsIn this study, a multi-omics analysis strategy combining single-cell RNA sequencing (scRNA-seq) and bulk RNA-seq was used to establish single-cell transcriptome profiles of tumor tissues from bladder cancer patients, focusing on B-cell populations and their interactions with other cell types in the tumor microenvironment. Large public databases were used to screen for key prognostic genes associated with bladder cancer B cells, and their biomarker expression was verified by in vitro experiments.ResultsBased on tumor samples from eight patients with bladder cancer and four normal samples, we selected 84, 967 cells for single-cell sequencing analysis. From these, we identified 10, 967 B cells and identified 508 key genes associated with B cells in bladder cancer from five different B cell subtypes. By integrating a large amount of RNA sequencing data, we identified VCL, FLNA, TAGLN, ACTA2, COL6A2, and CALD1 as potential biomarkers for B-cell-associated bladder cancer, and experimentally verified that these markers were significantly lower in bladder cancer patients than in the normal group, and were effective in predicting the survival rate of the patients and the status of the tumor immune microenvironment.ConclusionsUsing a combination of transcriptomic and experimental validation at single-cell and batch levels, this study provides insights into the key gene signatures of B cells from patients with bladder cancer and their roles in regulating the tumor immune microenvironment, providing new biomarkers and potential therapeutic targets for predicting patient’ prognosis and immunotherapy response.